A Classification for Some Small Chondrites in the Yamato-74 and -75 Meteorites - Miyamoto, Masamichi; Takeda, Hiroshi; Yanai, Keizo; Matsumoto, Yukio (1979)
P(論文) Electron microprobe studies have been made of olivines and pyroxenes in six Yamato chondrites collected in 1974 and 1975. On the basis of histograms of iron contents of olivines and pyroxenes, they are classified as follows : Yamato-(Y-) 75260 is a C2 carbonaceous chondrite; Y-74183 is an L6 ordinary chondrite; Y-74187,H6; Y-74198,H6; Y-74202,H5-6; and Y-74234,H4-5. In order to examine in detail the Mg-Fe chemical variation within the olivine or pyroxene grain found in some shocked ordinary chondrites, the Back-scattered Electron Image (BEI) observation has been carried out for several olivine grains in Yamato-74234. A larger percent mean deviation of olivine for these meteorites than what is expected from their texture, can be attributed to the presence of Fe-rich inclusions in the olivines. departmental bulletin paper